2017
DOI: 10.1186/s12263-017-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic effects of β-glucans from cauliflower mushroom and Lactobacillus fermentum on metabolic changes and gut microbiome in estrogen-deficient rats

Abstract: BackgroundWe investigated whether the long-term consumption of a symbiotic formulation with Lactobacillus fermentum (probiotic) and β-glucan from cauliflower mushroom (prebiotic) would delay the progression of post-menopausal symptoms in ovariectomized (OVX) rats and explored their mechanisms of action, including changes in gut microbiota.MethodsOVX rats were fed with high-fat diets containing 1% dextrin (control), 1% lyophilized cauliflower mushroom extract (CFM), 0.1% L. fermentum JS (LFE), 1% CFM plus 0.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Our further study revealed that amelioration of PCOS phenotype including hormonal disturbance may closely associated with the reduction of inflammation and the alteration of gut microbiota. In this paper, dietary inulin and metformin were demonstrated to possess capacity to alleviate PCOS throughout a series of routine indicators including pathological examination, reduced BWs, as well as rectification of abnormal hormones (T and E2), which were consistent with previous studies [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Our further study revealed that amelioration of PCOS phenotype including hormonal disturbance may closely associated with the reduction of inflammation and the alteration of gut microbiota. In this paper, dietary inulin and metformin were demonstrated to possess capacity to alleviate PCOS throughout a series of routine indicators including pathological examination, reduced BWs, as well as rectification of abnormal hormones (T and E2), which were consistent with previous studies [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…One of those articles was written in Japanese [ 21 ], seven in Korean [ 19 , 22 , 23 , 24 , 25 , 26 , 27 ], and the remaining in English. Among them, some studies demonstrated more than two healing effects of the mushroom [ 7 , 26 , 28 , 29 , 30 ]. Simultaneously, the anti-diabetic, anti-tumor, anti-inflammatory, anti-fungal, and antioxidant activities of S. crispa were reported in seven [ 6 , 12 , 14 , 28 , 29 , 30 , 31 ], nine-teen [ 7 , 13 , 15 , 21 , 23 , 24 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], four [ 7 , 22 , 30 , 42 ], three [ 19 , 29 , 43 ], and six [ 8 , 25 , 26 , 27 , 44 , 45 ] studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the triacylglycerol contents of the suspensions were assayed using a Trinder kit (Young Dong Pharm.) (10).…”
Section: Methodsmentioning
confidence: 99%